(3aJM GdhUjO aj TQM GdbUjOs - (3Yde GdOjf Ydj Hf eMeO GdSNGhj,J (B643 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd cJGHg GdYRjR fhQ fgJOi Hg EPG CXdeJ GdCehQ hHYO aEfi GPcQ ai gPG GdcJGH TQM bUjOI GdTjN GdTGWHi s
(3BNQgG (B:s
(3hbjd (B: (3jTHg hQbgG hQb GdWQaGA , UaQGA JTHg GdCJQL JSei CQLd GdLQGO dCfgG JTHggG hhRf RQfH (B: (3aYdd s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B332s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ HGdeOjfI GdefhQI(B((3bQGBJ (B46) s
Keywords: (3GdbQGAGJ hGdJLhjOs